Mapping frontiers across medieval Islam : geography, translation, and the'Abbasid Empire - Zadeh, Travis E. (London : I.B. Tauris, 2011)
The story of the 9th-century caliphal mission from Baghdad to discover the legendary barrier against the apocalyptic nations of Gog and Magog mentioned in the Quran has been either dismissed as superstition or treated as historical fact. By exploring the intellectual and literary history surrounding the production and early reception of this adventure, Travis Zadeh traces the conceptualization of frontiers within early'Abbasid society and re-evaluates the modern treatment of marvels and monsters inhabiting medieval Islamic descriptions of the world.
Includes bibliographical references (p. [262]-285) and index.
Keywords: Abbasids; Islamic Empire -- Historiography; Islamic Empire -- Historical geography